Influence of the COVID-19 Pandemic on Parenting Stress Across Asian Countries: A Cross-National Study - Kurata, Sawa; Hiraoka, Daiki; Ahmad Adlan, Aida Syarinaz; Jayanath, Subhashini; Hamzah, Norhamizan; Ahmad-Fauzi, Aishah; Fujisawa, Takashi X.; Nishitani, Shota; Tomoda, Akemi (Frontiers in Psychology, 2021)
Abstract Background. In a previous study, we demonstrated that the accumulation of parenting stress during prolonged school closures and restrictions on daily activities due to the COVID-19 pandemic in Japan indicates the need for mental health intervention for parents at higher risk of parenting stress. However, few studies have focused on parenting stress in other Asian countries, although they have experienced higher numbers of infections. The aim of the present study was to investigate whether parenting stress among caregivers increased across Asia due to school closures and restrictions on activities during the COVID-19 pandemic and to examine whether there were any country-specific, cross-country, or cross-regional risk factors for increased parenting stress. Methods. We conducted an online survey immediately after the number of new cases in India significantly increased (September to November 2020). We measured parenting stress, anxiety, and fear associated with the COVID-19 crisis, as evaluated by the Parenting Stress Index, Short-Form (PSI-SF) and the Coronavirus Anxiety Scale (CAS), across three Asian countries—India (n = 142), Malaysia (n = 69), and Japan (n = 182)—in addition to the US (n = 203). We also investigated whether respondents had adverse childhood experiences (ACE) as a risk factor for parenting stress. Results. For all countries, we found significant increases in participants’ current parenting stress levels, compared to what they recalled regarding their lives before COVID-19-related restrictions and school closures were enacted. Textual analysis qualitatively identified common terms related to parenting stress across all countries. We also found a statistical model that indicated ACE in parents was a critical risk factor for higher parenting stress via increasing anxiety and fear related to the pandemic. Conclusions. These results indicate the need to improve the mental health of caregivers who are at risk for higher levels of parenting stress during the COVID-19 pandemic in Asian countries as well as Western countries. These results indicate that there is a need to improve the mental health of caregivers who are at risk for higher levels of parenting stress during the COVID-19 pandemic globally.